2011
DOI: 10.12927/hcpol.2011.22351
|View full text |Cite
|
Sign up to set email alerts
|

A Global Approach to Evaluation of Health Services Utilization: Concepts and Measures

Abstract: Health services utilization has been the object of many books and papers in the literature. Measures associated with utilization are often a function of volume of services. The objective of this paper is to present a comprehensive approach to the evaluation of health services utilization and of associated measures, using databases. Based on the theoretical framework of starfield (1998), we analyze health services utilization with the help of indicators that are not directly linked to volume but that indirectly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…For instance, the literature review revealed that access was referred to opportunities, whereas utilization to the manifestation of these opportunities [1]. Moreover, differences in utilization could be either due to acceptable (e.g.…”
Section: The Pact Conceptual Framework For Mapping Access To Health Cmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the literature review revealed that access was referred to opportunities, whereas utilization to the manifestation of these opportunities [1]. Moreover, differences in utilization could be either due to acceptable (e.g.…”
Section: The Pact Conceptual Framework For Mapping Access To Health Cmentioning
confidence: 99%
“…Although the terms access, utilization, availability and universal coverage are used interchangeably in the literature in an effort to illustrate whether the health need of a patient is covered in an effective and timely manner, they refer to different elements of access to health care. Utilization appertains to ‘the outcome of the interaction between health professionals and patients' [1], while availability to the actual presence of health services delivery in terms of infrastructure, health personnel and utilization [2]. The WHO [3] defined universal coverage as ‘ensuring that all people can use the promotive, preventive, curative, rehabilitative and palliative health services they need, of sufficient quality to be effective, while also ensuring that the use of these services does not expose the user to financial hardship'.…”
Section: Introductionmentioning
confidence: 99%
“…Health care utilization is the result of the intercommunication between health care professionals and patients . More specifically, it is measured by the volume of services provided by health care professionals . Health care expenditure is defined as the costs associated with health services .…”
Section: Introductionmentioning
confidence: 99%
“…Health service utilization is an important issue in public health, and has been discussed in various fields, such as: health problems in developing countries; health economic issues, including health insurance; and health-care policy-making for health-care protection and health status. 5,6 Health disparities at the global, regional, and local scale can provide information about health problems and help improve health and well-being. Geographies of patients and health services are the main sources of information, being essential components of geographic information system (GIS) applications in public health.…”
mentioning
confidence: 99%